Model Pembiasaan Ungkapan Bahasa Arab sebagai Upaya Pengembangan Maharah Kalam Siswa Madrasah Ibtidaiyah - Wildatul Hasanah; Umar Manshur (FONDATIA, 2026)
Improving students’ maharah kalam through the habituation of using Arabic expressions in daily activities is an important aspect of creating communicative and applicative Arabic language learning at MI Ihyaul Islam. This study aims to describe and analyze the implementation of the Arabic expression habituation method in improving students’ maharah kalam at MI Ihyaul Islam. This study used a descriptive qualitative approach involving the madrasah principal, Arabic language teachers, and students as research subjects. Data were collected through observation, interviews, and documentation, then analyzed through the stages of data reduction, data presentation, and conclusion drawing. Data validity was tested using triangulation techniques. The results show that the continuous implementation of the Arabic expression habituation method was able to improve students’ speaking skills, particularly in the use of simple sentences in daily activities within the school environment. This improvement was evident in students’ confidence, fluency, and active participation in communicating in Arabic. The Arabic expression pocketbook served as a supporting medium that helped students understand, remember, and practice Arabic expressions independently. In addition, the contextual habituation of Arabic communication was able to form a simple bi’ah lughawiyah in the madrasah environment. This study concludes that the habituation method combined with the use of a pocketbook is effective in supporting the development of maharah kalam among Madrasah Ibtidaiyah students through direct communication practice in daily life. The implications of this study emphasize the importance of teachers’ consistency in integrating the habituation of Arabic expressions and the use of pocketbooks as supporting media to create an active, communicative, and student-centered language environment.